Multidisciplinary approach to a Marfan syndrome patient with emphasis on cardiovascular complications - Santavy, Petr (Biomedical papers, 2013)
Background: Marfan syndrome (MFS) is the most common inherited disorder of connective tissue affecting multiple organ systems. The most life-threatening and life-shortening complication is aortic dissection. Without surgery, life expectancy of MFS patients is reduced to approximately 32 years. Early identification and appropriate multidisciplinary medical cooperation is essential.Conclusion: Proper follow up, therapy and timely surgical repair lead to an almost normal lifespan in affected individuals.
Keywords: Marfan syndrome; aneurysms; aorta; aortic dissection; cardiovascular complications